Sistem Proteksi Dan Kontrol Pada Sensor Motor Menggunakan Face Rcognition - Pratama, Bagas; Savitri, Karlin; Sulistyo, Eko; Ocsirendi, Ocsirendi (Jurnal Inovasi Teknologi Terapan, 2025)
A motorcycle protection system based on Face Recognition was developed to improve security and prevent theft. This system combines protection key technology with a real-time location tracking feature connected via an Android application. NodeMCU is used as the main controller that integrates the GPS module to obtain motorcycle location data, while Firebase functions as a storage and processor of location data displayed on the application. This system is designed to control motorcycle electricity, including turning the motorcycle on and off via the application, while monitoring the location of the motorcycle with high accuracy. Testing was carried out to assess the function of key protection and motorcycle location tracking. The system has proven to have a fast response time and is reliable in controlling motorcycle electricity, both for one unit and several motorcycle units at once. Location tracking testing showed a success rate of 99% with a very low error of 0.0003%, while the data displayed on the application and Firebase has an accuracy of 100%. The results of the study show that this system can replace manual ignition with a better level of security. In addition, the location tracking feature provides additional benefits for users to monitor the position of the motorcycle in real time with accurate and reliable data.